Low-Complexity Error-Surface Prescribed Performance Control for Nonlinear Uncertain Single-Rod Electro-Hydraulic System - Wang, Wenbo; Liu, Shuang; Zhao, Dingxuan (IEEE transactions on control systems technology, 2024)
This brief presents a novel low-complexity error-surface prescribed performance control (ESPPC) for the single-rod electro-hydraulic system (EHS) subject to uncertain parameters and unknown nonlinearities. Different from existing results, the servo valve spool characteristic is considered to be nonlinear rather than linear. To solve the uncertain nonlinearities in the EHS, we propose a new control design approach by utilizing the error surface, the unknown dynamic estimator (UDE), and the prescribed performance methodology, which achieves prescribed transient and steady-state performance for the tracking error while avoiding the use of the backstepping scheme and the approximators [e.g., fuzzy systems (FSs) and neural networks (NNs)]. Moreover, to prevent the propagation of peak phenomenon induced by the UDE to the controlled system, the developed controller is appropriately saturated without impacting the prescribed performance properties of the tracking error. The stability of the EHS has been rigorously proved. Finally, extensive experimental results are offered based on a physical EHS to demonstrate the validity of the proposed approach.